Efektivitas Teknik Tiup-tiup dalam Mengurangi Kejadian Robekan Perineum pada Persalinan Normal - Roselia, Seli; Herawati, Teti; Anchopiah, Nida; Ristianingsih, Maya; Najilah, Lailatul; Nelawati, Nelawati (Faletehan Health Journal, 2026)
Vaginal birth in women, both at term and preterm, often results in uncomfortable experiences due to pain experienced during labor, one of which is perineal tears. One intervention that can be used to reduce pain during labor and reduce the occurrence of perineal tears is breathing technique of blowing during labor. This study aims to determine the effect of the blowing technique on the incidence of perineal tears in normal childbirth. The research design was a quasi-experiment with a non-equivalent control group design approach, comparing two groups of respondents, namely the intervention group that used the blowing technique and the control group that did not use the technique. A total sample of 60 respondents were selected using purposive sampling techniques, namely 30 people in the control group and 30 people in the intervention group. Bivariate analysis was performed using the chi-square test. The study results showed that the use of the blowing technique during labor resulted in fewer perineal tears (33.3%) compared to those delivering using the pushing technique (66.7%). The statistical test showed a p-value of 0.001 at α = 0.05, indicating a significant effect of the blowing technique on reducing the incidence of perineal tears. The blowing technique helps laboring mothers feel more relaxed, thereby reducing anxiety and pain. Thus, the risk of perineal tears can be reduced.